Proposta de um sistema de segurança eletrônica predial - Casillo, Danielle Simone da Silva (2004)
This work presents a suggestion of a security system of land automation having as objective main the creation of a system capable from easy method, supervise the installations of a building with the goal to preserver security personal and patrimonial necessities, aim at portability low cost and use easiness. Was designed an alarms central and access controller that has digital and analogical inputs for sensors and outputs for buzzer, telephonic dialing and electronic lock. The system is supervised by software that makes solicitations of information to the alarms central through the one computer's serial port (RS-232). The supervisory software was developed in platform LabVIEW with displays the received data on a graphical interface informing the sensors' current states distributed in the building and system events as alarns occurrences. This system also can be viewed through the Internet for people registered by the land security's system administrator